11.3k views
4 votes
A(n)=-5+6(n-1) Find the 12^(th ) term in the sequence.

User Bondsmith
by
6.7k points

1 Answer

3 votes

Final answer:

To find the 12th term in the sequence defined by a(n) = -5 + 6(n-1), we substitute n with 12 and calculate the expression to obtain the 12th term, which is 61.

Step-by-step explanation:

To find the 12th term in the sequence given by a(n) = -5 + 6(n-1), we substitute the term number n with 12:

a(12) = -5 + 6(12-1)
= -5 + 6(11)
= -5 + 66
= 61

Therefore, the 12th term of the sequence is 61.

User Izengod
by
6.9k points